Ecosystem Services and Fishery Production Dynamics of Wetland Ecosystem: An Appraisal of Alappuzha District of Kerala, India - Varkey, L. M.; Kumar, Pramod; Mridha, Nilimesh; Sekhar, I.; Sahoo, R. N. (Fishery Technology, 2016)
Wetlands serve as home to innumerable flora and fauna and deliver critical ecological and societal functions which often tend to get ignored during the developmental process. An assessment of ecosystem service contribution of wetlands of Alappuzha was attempted under benefit transfer framework to raise awareness regarding its invaluable contributions. The district being home to a network of backwaters falling under coastal lagoons, coastal natural wetands dominated the share. Erosion regulation and sediment retention, food production and recreation were the major ecosystem functions contributing to total ecosystem value. An assessment of growth and variability of inland fisheries, the major provisioning good of the wetlands, revealed the significance of Prawn, Etroplus and Tilapia in fish landings. Analysis of change in the area of Vembanad Lake during 2002-2014 revealed growing anthropogenic pressure, with a reduction of 465 ha of area. Fisheries of the lake has been seriously affected by continuing reclamation, pollution, eutrophication and anthropogenic interventions which have to be regulated to stop the decline of wetlands of the district.